Microbiology - Singh, R.P; Singh, R.P (Ludhiana Kalyani, 2005)
This book privides a balanced introduction to almost all major facets of microbiology ranging from fundamentals to applied.
Microbiology Microorganism Enzymes
Keywords: Microbiology, Microorganism, Enzymes